(Invited) Comparison of High Voltage, Vertical Geometry Ga2O3 Rectifiers with GaN and SiC. (3rd July 2019) - Yang, Jiancheng; Fares, Chaker; Carey, Patrick H; Xian, Minghan; Ren, Fan; Tadjer, Marko J.; Chen, Yen-Ting; Liao, Yu-Te; Chang, Chin-Wei; Lin, Jenshan; Sharma, Ribhu; Law, Mark E; et al.
Abstract : Ga2 O3 is a candidate for power electronics due to its large bandgap, controllable doping and availability of large inexpensive substrates. These include power conditioning systems, pulsed power for avionics and electric ships, solid-state drivers for heavy electric motors and advanced power management and control electronics. There are already cases where the performance exceeds the theoretical values for SiC. Existing Si, SiC (vertical devices), and GaN (lateral devices) enjoy advantages in terms of process maturity, especially for Si, where devices such as super-junctions surpass the unipolar "limit". Continued development of low defect substrates, optimized epi growth and improved device design and processing methods for Ga2 O3 are required to push the experimental results closer to their theoretical values. The actual experimental value of VB is well below the theoretical predictions. Thermal management is a key issue in Ga2 O3 power devices and initial studies have appeared on both the experimental and theoretical fronts.